Removal of Dyes by Aqueous Mixed Coagulants - Peik Yin Ooi; Tjoon Tow Teng; A. K. Mohd Omar; N. A. R. Nik Norulaini (Department of Chemical Engineering, Universitas Gadjah Mada, 2005)
Alum, MgCl2, and mixtures of alum and MgCl2 have been used as coagulant to remove coloring matter in the reactive dye Levafix Brill Blue EBRA. The jar test was used to determine the effectiveness and the optimal condition of the coagulation process in terms of pH of the coagulation process, coagulant dosage, percentage color removal, and floc settling time. Coagulant dosages of 1,000-5,000 ppm were studied. The treatment of textile industry wastewater was done in the treatment plant of a printing mill. The results showed that coagulation by MgCl2 and alum occurs at the removal pH ranges of 10.5-11.0 for MgCl2 and 4.0-6.0 for alum. The mixtures of MgCl2 and alum gave two distinct effective color-removal zones at pH 4-5.5 and pH 8-9.5. The addition of alum to MgCl2 shifted the optimal pH of MgCl2 from 10.5-11. 0 to 8. 0-9.5. The alum dose of 1,000-3,000 ppm in the coagulant mixture increased by 10-25 % the color removal in the alkaline zone. Floc settling time was found to (a) increase with coagulant dose and (b) take longer in the acidic color-removal zone than in the alkaline zone. The presence of alum increased the floc settling time in the alkaline zone. The study done at the treatment plant of a printing mill showed similar results. A mixture of 60% MgClz and 40% alum at an average dosage of 2,800 ppm gave a color removal of 97% and reductions of 88% for COD and 69% for suspended solids. Keywords: Chemical coagulation, color reduction, mixed coagulants, and textile waste.